2022
DOI: 10.1515/tsd-2022-2432
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of copper phthalocyanine pigment nanoparticles by eco-friendly ethoxylated cardanol in aqueous solution

Abstract: The environmentally friendly surfactant ethoxylated cardanol (EC) was investigated for dispersing copper phthalocyanine (CuPc) pigment nanoparticles into aqueous solution. The stability of the dispersion was investigated using UV-Vis spectra. The particle size was measured by optical microscopy, transmission electron microscopy and dynamic light scattering. The surface of the nanoparticles was characterised by measurements of the zeta potential and wettability. The coating application was investigated by incor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this case, the authors reported electrostatic stabilization would hardly be achieved, thus dispersion relied on steric stabilization. Overall, the zeta potential measurements of CuPc in various works are not high at −32 mV, −16 mV, and −25 mV meaning limited electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 88%
“…In this case, the authors reported electrostatic stabilization would hardly be achieved, thus dispersion relied on steric stabilization. Overall, the zeta potential measurements of CuPc in various works are not high at −32 mV, −16 mV, and −25 mV meaning limited electrostatic repulsion.…”
Section: Resultsmentioning
confidence: 88%